Perencanaan Produksi Menggunakan Kombinasi Model Integer Linear Programming Dan Model Simulasi (Studi kasus PT. Multi Strada Arahsarana) - Pambudi Seno Raharjo; Azizah Aisyati; Muh. Hisyam (Performa: Media Ilmiah Teknik Industri, 2005)
Production planning is a process to determine number of production in a particular period to fulfill consumers orders according to the available production capacity. Production planning by combining Integer Linear Programming (ILP) and simulation is done in iterative way. ILP has an objective function to minimize cost, which has a number of methods, such as reguler production capacity, overtime production capacity and inventory constrain, for each type of tyres for monthly during constraints in three month (January – March 2004). Simulation model representes stochastic events on the production floor, so that actual production capacity is obtained. On each iteration, number of production was compared with the available capacity from the result of simulation model. If the simulated number of production is more than or equal to the available capacity, the iteration need an adjustment capacity. And then, if the simulated number of production is less than the available capacity, the iteration is stopped, so that the number of production proper with the actual capacity is obtained.